Genetic variants in TMPRSS2 influence SARS-CoV-2 infection susceptibility within Mexican Mestizos - Montero, Rebeca I.; Dionicio, Cinthia L.; Noris, Gino; Piña-Pozas, Maricela; Santana, Carla; Gómez, Rocío (Frontiers in Genetics, 2025)
Since host genetics is one of the primary factors contributing to COVID-19 susceptibility and its clinical progression, several studies have focused on analysing the implications of genetic polymorphisms associated with COVID-19. These studies particularly emphasise on common variants in genes that are involved in the viral mechanism of host entry and in the host’s response to infection. In this study, we explored the participation of 24 single nucleotide polymorphisms located on the ACE, ADAM17, FURIN, IFITM3, TMPRSS2 and VDR genes in SARS-CoV-2 infection susceptibility. Three of these SNPs in TMPRSS2 (rs75603675, OR = 1.86, 95%CI = 1.29–2.66, p ≤ 0.001; rs4303795, OR = 1.98, 95%CI = 1.38–2.84, p ≤ 0.001 and rs8134378, OR = 2.59, 95%CI = 1.28–5.21, p ≤ 0.01) had a significant association with an increased risk of infection. When comparing haplotype frequency distributions, the haplotypes CAG (OR = 7.34, 95%CI = 5.51–9.77), AGA (OR = 2.46, 95%CI = 1.12–5.44), and AGG (OR = 1.59, 95%CI = 1.17–2.16) presented significant associations, suggesting that TMPRSS2 influences SARS-CoV-2 infection susceptibility within Mexican Mestizos. These risk alleles and their haplotypes were found more frequently in the case group than in the reference group, contributing to at least a twofold increase in the risk of SARS-CoV-2 infection, a finding that was reinforced by meta-analyses.